Quantitative Proteomic Analysis Reveals Antiviral and Anti-inflammatory Effects of Puerarin in Piglets Infected With Porcine Epidemic Diarrhea Virus - Wu, Mengjun; Zhang, Qian; Yi, Dan; Wu, Tao; Chen, Hongbo; Guo, Shuangshuang; Li, Siyuan; Ji, Changzheng; Wang, Lei; Zhao, Di; Hou, Yongqing; Wu, Guoyao (Frontiers in Immunology, 2020)
Porcine epidemic diarrhea virus (PEDV) has caused enormous economic losses to the swine industry worldwide in recent years. Puerarin (PR) has been reported to exert an antiviral effect. This study was conducted with both PEDV-infected Vero cells and neonatal pigs to determine the effect of PR on PEDV infection and to elucidate the underlying mechanisms by a proteomic analysis. Twenty-four piglets fed a milk replacer were randomly allocated into one of three groups (Control, PEDV, and PEDV+PR). After a 5-day period of adaption, piglets (n = 8/group) in the PEDV+PR were orally administered with PR (0.5 mg/kg body weight) between days 5 and 9, whereas piglets in the other two groups received the same volume of liquid milk replacer. On day 9, piglets were orally administered with either sterile saline or PEDV (Yunnan province strain) at 104.5 TCID50 (50% tissue culture infectious dose) per pig. On day 12 of the trial, jugular vein blood and intestinal samples were collected. In addition, Vero cells were assigned randomly into three groups (Control, PEDV, PEDV+PR). Cells in the PEDV and PEDV+PR groups were infected with PEDV at a multiplicity of infection of 0.01, while cells in the control group were treated with the same volume of sterile saline. One hour later, cells in the Control and PEDV groups were cultured in serum-free DMEM, while those in the PEDV+PR group were supplemented with PR solution. After 36 h of culture, cells were harvested. PR attenuated the reductions of cell proliferation in vitro and growth performance in PEDV-infected piglets, and inhibited PEDV replication and the expression of several cytokines (including IL-8) both in vitro and in vivo. Proteomic analyses showed that the abundance of 29 proteins in the ileum was altered by PEDV infection and was restored to the control level by PR. Pathway analyses revealed that PR restored the expression of several interferon-stimulated genes and selectively upregulated the expression of guanylate binding proteins. Western blot analyses showed that PR supplementation inhibited the PEDV-induced NF-κB activation. Collectively, these results indicate PR could exert antiviral and anti-inflammatory effects in piglets infected with PEDV.